Citizens and Subjects : The Netherlands, for example - Braidotti, Rosi; Esche, Charles; Hlavajova, Maria; Bracke, Sarah; Ghorashi, Halleh; Captain, Esther; Oosterling, Henk; Prins, Baukje; van der Tuin, Iris; Biennale di Venezia Venetië 2007 (Utrecht : BAK, basis voor actuele kunst, 2007)
Dumas, Marlene ; Moti, Melvin ; Kinoshita, Suchan ; Mik, Aernout ; Weiner, Lawrence ; de Rooij, Willem ; Tabatabai, Nasrin ; Afrassiabi, Babak
A Critical Reader, published as part of the project Citizens and Subjects, the Dutch contribution to the 52nd International Art Exhibition - La Biennale di Venezia, Dutch Pavilion, Venice, 10 June - 21 November 2007 ; as an extension of the Pavilion taking place in the Netherlands in autumn 2007
boek